Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.1093/carcin/bgt390
|View full text |Cite
|
Sign up to set email alerts
|

WNT5A-mediated  -catenin-independent signalling is a novel regulator of cancer cell metabolism

Abstract: WNT5A has been identified as an important ligand in the malignant progression of a number of tumours. Although WNT5A signalling is often altered in cancer, the ligand’s role as either a tumour suppressor or oncogene varies between tumour types and is a contemporary issue for investigators of β-catenin-independent WNT signalling in oncology. Here, we report that one of the initial effects of active WNT5A signalling in malignant melanoma cells is an alteration in cellular energy metabolism and specifically an in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
52
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(56 citation statements)
references
References 57 publications
(72 reference statements)
4
52
0
Order By: Relevance
“…Furthermore, my colleagues and I have found that WNT5A, signaling by the Ca 2ϩ /WNT signaling pathway in melanoma cells, also increases aerobic glycolysis, mediated by the AktmTORC1 signaling module (13). Collectively, this work suggests that WNT/Akt-mTOR signaling is an important step in controlling cancer cell metabolism in a variety of tumor types.…”
Section: Noncanonical Wnt Signaling and Cancer Cell Metabolismmentioning
confidence: 74%
See 2 more Smart Citations
“…Furthermore, my colleagues and I have found that WNT5A, signaling by the Ca 2ϩ /WNT signaling pathway in melanoma cells, also increases aerobic glycolysis, mediated by the AktmTORC1 signaling module (13). Collectively, this work suggests that WNT/Akt-mTOR signaling is an important step in controlling cancer cell metabolism in a variety of tumor types.…”
Section: Noncanonical Wnt Signaling and Cancer Cell Metabolismmentioning
confidence: 74%
“…My colleagues and I have found that WNT5A signaling alters carbohydrate metabolism with directly opposite effects on breast cancer and melanoma cells, increasing OXPHOS in the former and aerobic glycolysis in the latter (13), which correlate with reduced and enhanced survival of patients, respectively. So, although most of the WNT signaling pathways studied to date result in enhanced aerobic glycolysis in cancer cells (Fig.…”
Section: Future Perspectivementioning
confidence: 99%
See 1 more Smart Citation
“…The upregulated expression of GLUT1 decreased the expression of WNT5A, the signaling of which in malignant melanoma cells alters cellular energy metabolism and specifically increases aerobic glycolysis (33). In a recent study, WNT5A was suggested to promote melanoma cell migration/invasion via an FZD-4-β-catenin-dependent mechanism (34).…”
Section: Discussionmentioning
confidence: 99%
“…(66,67) Another study dealing with changes in energy metabolism found WNT5A to increase the aggressive behavior of melanoma cells beyond the enhancement of aerobic glycolysis. (68) In contrast, downregulation of WNT5A showed inhibitory effects on melanoma cell invasion. (69) Different studies indicate that WNT5A is regulated by the pro-inflammatory cytokine interleukin-6 (IL-6) in a p38a-MAPK-dependent manner.…”
Section: Melanomamentioning
confidence: 99%